BTS-BI APPLICATION (INDONESIAN STUDENT TEXT BOOK) BASED ON ANDROID - Endah Riski Kartini; Sri Budi Utami; Opie Octaviana Sari (STAI Hubbulwathan Duri, 2020)
This research aims to develop, design, and create innovations in education that can be used in learning, namely Android-based BTS-BI applications that can be used to facilitate teachers and students in implementing the learning process. If teachers and students cannot attend class learning, this application can be utilized. The research method used is a qualitative descriptive approach that was developed using a research and development model. The results of this study are Android-based